A case of ureteral orifice obstruction by bladder indwelling catheter - Kazuma Tsuboi; Kosuke Hino; Shin Kanemoto; Yasuhiro Nishiyama; Ryoji Arata; Noriaki Ono (Urology Case Reports)
A 91-year-old man with a long-term bladder indwelling catheter (BIC) for benign prostatic hyperplasia (BPH) presented to our emergency department with fever.Computed tomography (CT) showed the tip of the BIC was located within the left ureterovesical junction, which caused left hydronephrosis and a hydroureter.The catheter was replaced, and the hydronephrosis improved quickly.The patient was treated with antibiotic therapy and discharged on day 10.Catheterization is one of the most common procedures performed by urologists; however, it can lead to unexpected complications.